Anti-MYC-associated zinc finger protein antibodies are associated with inflammatory atherosclerotic lesions on 18F-fluorodeoxyglucose positron emission tomography. (April 2017) - Ernst, Diana; Weiberg, Desiree; Baerlecken, Niklas T.; Schlumberger, Wolfgang; Daehnrich, Cornelia; Schmidt, Reinhold E.; Bengel, Frank M.; Derlin, Thorsten; Witte, Torsten
Abstract: Background and aims: Atherosclerosis is a chronic inflammatory process of vessel walls responsible for coronary, cerebrovascular and peripheral vascular disease, which together account for the majority of non-infective global deaths. Whilst great emphasis has been placed on lifestyle factors, a growing body of evidence supports an autoimmune component to atherosclerosis. This study evaluates a novel autoantibody against MYC-associated zinc finger protein (MAZ-Ab) as a potential marker of atherosclerosis. It compares MAZ-Ab to activity on whole-body positron-emission tomography/computed tomography (PET/CT) attributable to atherosclerosis. Methods: Antibody screening using protein arrays was performed in patients with angiographically-proven ischaemic heart disease. Following MAZ-Ab detection, an ELISA for large-scale testing was developed. An a priori group of unselected patients attending for unrelated 18 F-fluorodeoxyglucose (FDG) PET/CT was prospectively enrolled. Each completed a structured questionnaire under supervision and provided serum for analysis. PET/CT scans were evaluated for inflammatory arterial lesions. Whole-body arterial inflammatory burden was then correlated with ELISA optical density for MAZ-Ab. Results: Protein array testing identified IgG anti-MAZ antibodies in 4/6 (67%) patients with ischemic heart disease, versus 0/10 controls. Significant positive correlations between MAZ-Ab and both increasing number of PET positive inflammatory atherosclerostic lesions ( p = 0.023) and whole-body arterial inflammatory burden ( p = 0.002) were shown. No traditional atherosclerotic risk factor correlated with MAZ-Ab. Conclusions: A quantitative association between MAZ-Ab optical density on ELISA and the cumulative inflammatory burden of atherosclerosis on 18 F-FDG PET/CT could be shown. These findings provide further evidence for an autoimmune component in atherosclerosis and suggest MAZ-Abs as a potential biomarker for atherosclerotic disease. Highlights: MAZ upregulates MMP-14 expression in atherosclerotic plaque macrophages. PET/CT provides validated all-body visualization of inflammatory atherosclerotic lesions. Serum MAZ-Ab correlates with "all-body" inflammatory atherosclerotic lesions on 18 F-FDG PET/CT. Elevations in MAZ-Ab titre were independent of traditional cardiac risk factors.